2010
DOI: 10.1111/j.1582-4934.2010.01141.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of epicardial and perivascular adipose tissue in the pathophysiology of cardiovascular disease

Abstract: Obesity, insulin resistance and the metabolic syndrome, are characterized by expansion and inflammation of adipose tissue, including the depots surrounding the heart and the blood vessels. Epicardial adipose tissue (EAT) is a visceral thoracic fat depot located along the large coronary arteries and on the surface of the ventricles and the apex of the heart, whereas perivascular adipose tissue (PVAT) surrounds the arteries. Both fat depots are not separated by a fascia from the underlying tissue. Therefore, fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
158
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(164 citation statements)
references
References 121 publications
(272 reference statements)
2
158
0
4
Order By: Relevance
“…47 The anatomic location of EF, without Cardiac adiposity and heart function in obesity B Gaborit et al any barrier to the adjacent myocardium, allows local paracrine interactions between EF and the myocardium. 48 EF could directly supply myocardial cells with fatty acids. Furthermore, it is suggested that inflammatory signals produced by EF, associated with low levels of adiponectin, may increase the membrane localization of CD36 in cardiomyocytes and consequently increase myocardial lipid uptake.…”
Section: Discussionmentioning
confidence: 99%
“…47 The anatomic location of EF, without Cardiac adiposity and heart function in obesity B Gaborit et al any barrier to the adjacent myocardium, allows local paracrine interactions between EF and the myocardium. 48 EF could directly supply myocardial cells with fatty acids. Furthermore, it is suggested that inflammatory signals produced by EF, associated with low levels of adiponectin, may increase the membrane localization of CD36 in cardiomyocytes and consequently increase myocardial lipid uptake.…”
Section: Discussionmentioning
confidence: 99%
“…As compared to other adipose depots, EAT is characterized by smaller adipocytes and greater adipocyte number per gram of tissue, and differences in protein and fatty acid composition have also been reported [18].…”
Section: Fat Depots Around the Heartmentioning
confidence: 99%
“…In addition, Ouwens et al have demonstrated an increased expression of omentin in the epicardial tissue. The authors presume that omentin counteracts the formation of atheromatous plaque in coronary vessels and has a beneficial effect on other disorders pathogenetically linked to obesity, such as arterial hypertension, in relation to the omentin-induced vasodilatory effect [32]. A negative correlation has been identified between the concentration of omentin and the thickness of the intima-media complex in carotid arteries, their stiffness, BMI, waist circumference, systolic arterial pressure, fasting blood glucose level and the insulin resistance index HOMA-IR (homeostasis model assessment of insulin resistance).…”
Section: Omentynamentioning
confidence: 99%
“…wykazali zwiększoną ekspresję omentyny w tkance nasierdziowej. Autorzy ci przypuszczają, że adipokina przeciwdziała tworzeniu się blaszki miażdżycowej w naczyniach wieńco-wych oraz korzystnie wpływa na inne zaburzenia patogenetycznie powiązane z otyłością, takie jak nadciśnienie tętnicze, w związku z wykazywanym przez nią efektem wazodylatacyjnym [32]. Stwierdzono negatywną korelację stężenia omentyny z grubością kompleksu intima-media tętnic szyjnych, ich sztywnością, BMI, obwodem talii, skurczowym ciśnieniem tętniczym, stężeniem glukozy na czczo oraz wskaź-nikiem insulinooporności HOMA-IR (homeostasis model assessment of insulin resistance).…”
Section: Omentynaunclassified